Digital vs paper-based checklists in high performance single pilot aircraft : a mixed methods investigation : a 190.895 (60 credit) research report presented in partial fulfilment of the requirements for the degree of Master of Aviation at Massey University, Palmerston North, New Zealand - Barron, Peter (Massey University, 2022)
The aircraft checklist has been described as the most critical man-machine interface in aviation. Checklists can significantly enhance flight safety when designed well and used properly. The ‘look’ and content of a checklist affects how well pilots interact with it. Emergency checklists in particular, are only accessed during emergency situations, a time of heightened stress and cognitive degradation for the pilot. It is crucial therefore, that emergency checklists are developed with precision and skill to facilitate ease of use during times of stress. A poorly designed checklist can hinder rectification of an emergency situation and can adversely affect flight safety. The aim of this study was to determine whether flying performance is improved, and pilot workload is lower, when using a digital checklist application created specifically for the T-6C Texan II compared with the existing paper-based Quick Reference Handbook (QRH). For this study, twenty pilots from the Royal New Zealand Air Force (RNZAF) underwent two emergency scenarios in a flight simulator using either the QRH or the digital checklist application. The independent variable was checklist type (paper or digital). Dependent variables were: i) time to find the checklist; ii) time to complete the checklist; iii) flight path accuracy; and iv) workload. Additionally, a qualitative investigation into error occurrences during checklist execution was undertaken. The results suggested that workload is lower when using the digital checklist application compared to the QRH, but there were mixed results regarding the improvement in flying performance with the digital checklist application. The time to find the checklist was quicker with the digital application, but checklist completion times and flight path accuracy were similar across both checklist types. The qualitative investigation noted that the digital checklist reduced errors and was easier to manipulate. The collection of qualitative data enabled the generation of a hypothesis that frequency and type of error occurrences are affected by checklist type. Despite the interface improvements of the digital checklist over the QRH, this research suggests that an enhanced checklist interface is secondary to checklist location or checklist content, and that the greatest gains in safety will likely be achieved by addressing these two factors over checklist interface. This research provides support for an iPad mount in front of the pilot in the T-6C. Additionally, this research provides further evidence that the T-6C checklist content is poorly written and can negatively impact flight safety and may assist in arguing for a content re-write. From a wider perspective, most RNZAF pilots fly with a kneeboard and this research may be relevant for other aircraft types operated by the RNZAF, noting also that other aircraft types are flown by two pilots which may negate some of the findings in this research. Further research should standardise the placement of the checklist to fully determine the relationship between flying performance and checklist type. Additionally, future research could also make use of eye tracking equipment to measure attention switching and could investigate the hypothesis generated from the qualitative data.
Keywords: Airplanes; Piloting; Aeronautics; Safety measures; 400103 Aircraft performance and flight control systems